PENGARUH GAYA KEPEMIMPINAN, KNOWLEDGE MANAJEMEN DANA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KANTOR PELAYANAN PAJAK PRATAMA JAKARTA KEBAYORAN BARU II - Riska Nur Cahyani; Roby Wijaya (Pasca Sarjana Universitas Satya Negara Indonesia, 2015)
This research purpose was to analyze and assess the influence of leadership style, knowledge management and discipline of work on employee performance Jakarta tax office pratama Kebayoran baru II. This research type is a quantitative study with explanatory survey methods and data collection tools used questionnaires. The results of this study concluded the style of leadership, knowledge management and discipline of employees working on the performance of Jakarta tax office pratama Kebayoran baru II, either jointly or individually. Where the value of the correlation coefficient leadership style (X1), knowledge management (X2) and discipline (X3) on the performance of employees is 0.824, meaning the leadersip style (X1), knowledge management (X2) and discipline (X3) has a very strong relationship on employee performance and test results determinant coefficient (R2) value of 0.678 which can be obtained disimpulakan style kepemimpianan (X1), knowledge management (X2) and discipline (X3) contributed by 67.80%% of the increase in employee performance, while the remaining 32 , 20% are influenced by other factors not examined in this research.